Redefining Privity of Contract: The Untapped Rights of Consumers in Goods Delivery Agreements: Mendefinisikan Ulang Privity of Contract: Hak-hak Konsumen yang Belum Tersentuh dalam Perjanjian Pengiriman Barang - Qois, Ghozi Naufal; Chumaida, Zahry Vandawati; Subagyono, Bambang Sugeng Ariadi (Rechtsidee, 2023)
This study critically analyses the entrenched concept of the privity of contract doctrine within the context of goods delivery agreements and its impact on the final consumer, specifically focusing on issues of delayed delivery and consequential losses. Adopting normative legal research methodologies, it employs statutory, conceptual, and case-based approaches to dissect this complex consumer protection issue. The research reveals that while the privity of contract paradigm posits rights and obligations as exclusive to the contracting parties, the final consumer, as the recipient of goods, possesses legal standing in cases of delivery negligence or incurred losses. The study also highlights the consumer's right to delivery in accordance with the agreed terms, even when not a primary party in the agreement, as long as the goods are not for resale. The paper concludes by emphasizing the critical role of judges in assessing immaterial losses based on the principle of ex aequo et bono, thus underscoring a shift towards a caveat vendor approach in consumer law, with significant implications for both business actors and global consumer protection frameworks. Highlights: The concept of privity of contract is not absolute in goods delivery agreements, and the final consumer can possess legal standing in cases of delivery negligence or incurred losses. The recipient of goods, even when not a primary party in the agreement, maintains the right to delivery in accordance with the agreed terms, provided the goods are not intended for resale. Judges play a pivotal role in quantifying immaterial losses, underlining the shift towards a caveat vendor approach in consumer law. Keywords: Privity of Contract, Consumer Protection, Goods Delivery Agreements, Legal Standing, Ex Aequo et Bono.